Violence and free will in the story The plain in flames of Juan Rulfo: the will to power as a backdrop in the mexican revolution - Elton Emanuel Brito Cavalcante (Travessias, 2018)
One of the controversial themes of the last century is the Mexican Revolution, so important for the formation of the current political, economic and artistic paradigm of that country. Juan Rulfo is one of the first writers to analyze it in an impartial way, especially in the story The Plain in Flames. This story describes several types of violence, so in this work the following topic is analyzed: Is the protagonist of the story a violent man because he wants it or because it is his nature? To answer this question, we will start from the philosophical and religious concept of "evil" in itself until we reach the notion of social evil.